Aplikasi Sistem Penerimaan Siswa Baru SMK Taruna Bakti Cikarang Selatan Berbasis Web dengan Metode Rapid Application Develoment (RAD) - Marianus Yoman Bilo Poso; NM Faizah; Panser Karo Karo (Design Journal, 2023)
New student enrollment is a process that exists in government educational institutions such as schools to help screen prospective students and incoming students who are selected as students according to criteria set by the school. In general, the admission process for new students goes through the stages of registration, selection test, admission of students and students. In this study, the application to SMK Taruna Bakti Cikarang Selatan was done manually or by computer, but because Microsoft Office Excel was used, there was a lot of missing data and manual calculation of the test results could lead to errors. there is. The formulation of this research problem is how to create an information system for admission of new students in SMK Taruna Bakti Cikarang Selatan. The research methodologies used are Rapid Application Development (RAD), Observation, Analysis, Design, Testing, and Implementation. This new information system for student enrollment is written in the PHP programming language and uses a MySQL database as the database server. The outcome of this research is her web-based her first-year information that makes it easy for a prospective student and her first-year parent to obtain all information about her first-year and complete online registration system.